EFEKTIVITAS AUGMENTED REALITY DAN VIRTUAL REALITY PADA PENDIDIKAN KEJURUAN: SYSTEMATIC LITERATURE REVIEW - Muhammad Yasser Arafat; Hakkun Elmunsyah; Bastian Rikardo Parhusip (Steam Engineering, 2026)
The purpose of this study is to analyse the effectiveness of using Augmented Reality (AR) and Virtual Reality (VR) in vocational education. This study addresses the need for a comprehensive understanding of the impact of immersive technology on improving the quality of learning in various vocational fields. The research methodology applied was a Systematic Literature Review of 40 articles, consisting of 16 quasi-experimental designs, 13 randomised controlled trials, 7 mixed methods, 3 observational studies, and 1 case study. Of the articles studied, 23 studies used VR technology, 12 studies used AR, and 5 studies used a combination of both. The educational contexts analysed covered various fields, with nursing being the most studied field with 6 studies. The main findings show significant effectiveness in various aspects of learning. In orthopaedic surgery training, a transfer effectiveness ratio of 0.79 was found. In construction safety training, hazard identification accuracy reached 78.3% using VR, compared to 18.5% with traditional methods. Student engagement levels also showed positive results, with 100% of students reporting an increase in interest in learning, and 92% of students reporting good confidence levels in the VR training group. This study makes a significant contribution to the field of education by presenting empirical evidence regarding the effectiveness of AR and VR in vocational learning. The study also identified factors for successful implementation, including the importance of integrating this technology with appropriate pedagogical strategies, as well as its potential to improve educational accessibility. Despite challenges such as high initial costs and technical issues, the results of the study show that AR and VR are effective learning media for improving the quality of vocational education, especially in learning complex and high-risk skills.